ANALISIS NILAI TAMBAH DAN PEMASARAN PRODUK AGROINDUSTRI KELAPA (COCOS NUCIFERA L.) PADA PERUSAHAAN WOOTAY COCONUT - Lawalata, Marfin; Imimpia, Rika (JURNAL AGRICA, 2020)
The Wootay Coconut Company is a company engaged in the field of coconut production which was established in 2018. The coconut production process changes the primary form into a new product with higher economic value after going through processing, and can provide added value due to costs incurred so that prices are formed new higher and greater profits when compared without going through processing. This research aims to determine the characteristics, added value and level of income of Wootay Coconut company, Teon Nila Serua Subdistrict, Central Maluku Regency. The method used is the measurement of added value based on the Hayami method, then the analysis of income for coconut raw material products.  The results of the study showed that the added value in Copra was IDR 2,600, - value added ratio of 42.62%. Nata De Coco small size added value of IDR 311,100, - the ratio of value added 99.33% while for large size added value of  IDR 296,191.68, - value added ratio of 90.30%. Virgin Coconut Oil (VCO) small size of IDR 515,250, - value added ratio of 99.33%, medium size of value added of IDR 577,500, - the ratio of value added 99.40% while the large size of the added value of IDR 634,960.9, - value added ratio of 99.45% of the production value. The overall income of the Wotay Coconut Company generates a monthly net income of  IDR 55,117,833.